TEACHING ENGLISH FOR NET GENERATION THROUGH VIRTUAL REALITY ASSISTED LANGUAGE LEARNING IN EFL CLASSROOM - Herwiana, Sakhi; Munir, Ahmad (Universitas Negeri Malang, 2024)
This paper aims to give insight and recommend teachers to implement Virtual Reality in language learning, especially in EFL classrooms such as in Indonesia. In the digital era, the use of technology by young people cannot be separated from daily life. Therefore, teachers can use and create the course materials by implementing virtual reality in building language acquisition instead of using traditional methods and textbooks. Using interesting learning sources can enhance students’ motivation to learn. The use of Virtual Reality will give new experiences and environments for the students to learn a new language especially English.